Effect of feeding detoxified Jatropha curcas meal on carcass characteristics and meat quality in lambs - PATIL, S S; SHARMA, K; DUTTA, NARAYAN; PATTANAIK, A K; MENDIRATTA, S K (The Indian Journal of Animal Sciences, 2015)
Lambs (24) of about 3 to 4 months of age with an average body weight of 15.76±1.92 kg were divided randomly into 4 groups of 6 each as per completely randomized design and allocated to 4 dietary treatments dJM-0, dJM- 12.5, dJM-25 and dJM-37.5. Lambs in dJM-0 were fed with concentrate mixture containing soybean meal as the major protein source, while those from the rest of the 3 groups were fed concentrate mixtures containing detoxified jatropha meal (dJM) replacing soybean meal of control at 12.5, 25.0 and 37.5% level, respectively, on iso-nitrogenous basis. The lambs were scarified after 180 days of experimental feeding. The voluntary feed intake of lambs did not differ significantly among the dietary treatments. Pre-slaughter weight (PSW), carcass yield, carcass length and loin eye area of lambs were similar between control and treatment groups. Similarly, yield of wholesale cuts, edible and non-edible visceral organs were comparable among groups. Chemical composition, physico-chemical properties and phorbol esters concentration of Longissimus dorsi (LD) muscle did not differ significantly among groups. Organoleptic scores and tenderness of pressure cooked LD muscle samples with salt (1.5% w/w) were also comparable among the treatment groups. It may be concluded that soybean meal cake can be replaced with detoxified jatropha meal up to 37.5% in the diet of growing lambs without any apparent adverse impact on carcass yield and meat quality.